2016
DOI: 10.5507/bp.2016.046
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cholangiopancreatography (MRCP) using new negative per-oral contrast agent based on superparamagnetic iron oxide nanoparticles for extrahepatic biliary duct visualization in liver cirrhosis

Abstract: Background and Aims. Magnetic resonance cholangiopancreatography (MRCP) is often used for imaging of the biliary tree and is required by surgeons before liver transplantation. Advanced liver cirrhosis and ascites in patients however present diagnostic problems for MRCP. The aim of this study was to find out if the use of our negative per-oral contrast agent containing superparamagnetic iron oxide nanoparticles (SPIO) in MRCP is helpful for imaging of hepatobiliary tree in patients with liver cirrhosis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several negative oral contrast agents for MRCP that render the bowel signal dark on T2-weighted sequences are commercially available [i.e., ferumoxsil (GastroMARK; Mallinckrodt Inc., Raleigh, NC, USA), manganese chloride, barium sulfate, and ferric particles] ( 20 , 21 ). Previous studies using these agents also showed the correlative results with our study for the improvement of visibility of biliary ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Several negative oral contrast agents for MRCP that render the bowel signal dark on T2-weighted sequences are commercially available [i.e., ferumoxsil (GastroMARK; Mallinckrodt Inc., Raleigh, NC, USA), manganese chloride, barium sulfate, and ferric particles] ( 20 , 21 ). Previous studies using these agents also showed the correlative results with our study for the improvement of visibility of biliary ducts.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Simone et al, a patient with CCA was successfully identified by blind evaluation using SPIO [ 54 ]. Polakova et al indicated that oral SPIO negative contrast agent administered before MRCP improved the display rate of the extrahepatic bile duct, especially for patients with ascites [ 55 ].…”
Section: Mr Imagingmentioning
confidence: 99%
“…(Mania et al, 2011;Arif-Tiwari et al, 2014;Yeom et al, 2015). (Mania et al, 2011;Polakova et al, 2016).…”
Section: εργαστηριακά ευρήματαmentioning
confidence: 99%